Body mass and Abdominal Profile Index in captive Hawaiian Geese - Zillich, U; Black, J (Wildfowl, 2014)
It is often not practical or desirable to collect birds to assess their body mass. The Abdominal Profile Index (API), developed by Owen (1981), is an alternative method that can be used without capturing or collecting animals. The weight and API scores (from 0 - 4 points) of captive Hawaiian Geese Branta sandvicensis were recorded every two weeks for a year. API was significantly correlated with mass and mirrored even minor changes in this parameter. The corresponding mass change per half point on the A P index was 85g for females and 115g for males during the non-breeding season. This is equivalent to 4.0 % of the female and 4.8 % of the male mean body mass during the non-breeding season.